Fibrinolytic potential as a risk factor for postpartum hemorrhage - Gruneberg, Daniel; Braun, Paula; Schöchl, Herbert; Nachtigall-Schmitt, Tereza; von der Forst, Maik; Tourelle, Kevin; Dietrich, Maximilian; Wallwiener, Markus; Wallwiener, Stephanie; Weigand, Markus A.; Fluhr, Herbert; Spratte, Julia; et al. (Frontiers in Medicine, 2023)
Background: Postpartum hemorrhage is still the leading cause of maternal morbidity and mortality worldwide. While impaired fibrin polymerization plays a crucial role in development and progress of PPH, recent approaches using viscoelastic measurements failed to detect early changes of fibrinolysis in PPH sensitively. The aim of this study was to evaluate whether women suffering from PPH show alterations in POC-VET fibrinolytic potential during childbirth and if fibrinolytic potential offers benefits in prediction and treatment of PPH. Methods: Blood samples were collected at three different timepoints: T0 = hospital admission (19h ± 18h prepartum), T1= 30-60 minutes after placental separation and T2 = first day postpartum (19h ± 6h postpartum). Beside standard laboratory tests, whole-blood impedance aggregometry (Multiplate), viscoelastic-testing (VET) performed by the ClotPro system, including TPA-test lysis time to assess POC-VET fibrinolytic potential, as well as selected coagulation factors were measured. Results were correlated with markers of blood loss and clinical outcome. Severe PPH was defined as hemoglobin drop > 4g/dl and/or occurrence of shock or need for red blood cell transfusion. Results: Blood samples of 217 parturient women between June 2020 and December 2020 at Heidelberg University Women's Hospital were analyzed and 206 measurements were eligible for the final analysis. Women suffering from severe PPH showed increased fibrinolytic potential at hospital admission already. The difference in comparison to non PPH persists 30-60min after placental separation. Higher fibrinolytic potential was accompanied by greater drop of fibrinogen and higher d-dimer values after placental separation. While fibrinolytic potential was increased in 70% of women suffering from severe PPH, 54% of patients without PPH showed increased fibrinolytic potential as well. Conclusion: We were able to show that ante- and peripartal fibrinolytic potential was elevated in women suffering from severe PPH. However, several women showed high fibrinolytic potential, but lacked clinical signs of PPH. Indicating that high fibrinolytic potential is a risk factor for the development of coagulopathy, but further conditions are required to cause PPH.